Humoral immune responses against the malaria vaccine candidate antigen Plasmodium vivax AMA-1 and IL-4 gene polymorphisms in individuals living in an endemic area of the Brazilian Amazon - Moreira Batista Tomaz, Franciele Maira; Cruz Furini, Adriana Antonia da; Capobianco, Marcela Petrolini [UNESP]; Povoa, Marinete Marins; Alves Trindade, Pamella Cristina; Fraga, Valeria Daltibari; Conceicao, Luciana Moran; Azevedo, Lucas Ribeiro de [UNESP]; Oliani, Sonia Maria [UNESP]; Cassiano, Gustavo Capatti [UNESP]; Cavasini, Carlos Eugenio; Batista dos Santos, Sidney Emanuel; et al. (Elsevier B.V., 2015)
Background: Several studies have recently demonstrated that the immune responses against malaria is governed by different factors, including the genetic components of the host. The IL-4 gene appears to be a strong candidate factor because of its role in the regulation of the Th2 response. The present study investigated the role of IL-4 polymorphisms in the development of IgG antibodies against PvAMA-1 and the IL-4 levels in individuals infected with Plasmodium vivax in a malaria endemic area in the Brazilian Amazon.Methods: The study sample included 83 patients who were diagnosed with P. vivax infection using thick smear and confirmed by nested-PCR. The IL-4 590 C>T and IL-4 33 C>T polymorphisms were genotyped by PCR-RFLP, and the intron 3 VNTR was genotyped by PCR. A standardised ELISA protocol was used to measure the total IgG against PvAMA-1. The cytokine/chemokine levels were measured using a Milliplex multiplex assay (Millipore). All of the subjects were genotyped with 48 ancestry informative markers to determine the proportions of African, European and Amerindian ancestry using STRUCTURE software.Results: Of the 83 patients, 60 (73%) produced IgG antibodies against PvAMA-1. A significant decrease in the percentage of respondents was observed among the primo-infected individuals. No significant differences were observed in the frequencies of genotypes and haplotypes among individuals who were positive or negative for IgG antibodies against PvAMA-1. Furthermore, no significant correlation was observed between the IL-4 polymorphisms, antibody levels, IL-4 levels, and parasitemia.Conclusions: This study indicated that the polymorphisms identified in the IL-4 gene are not likely to play a role in the regulation of the antibody response against PvAMA-1 and IL-4 production in vivax malaria. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Plasmodium vivax; Interleukin 4; Ancestry informative markers; Parasitemia; SNP